Thermoanalytical study of cassava starch native and treated with hydrogen peroxide - Costa, Fernanda Janaina Oliveira Gomes da; Almeida, Rafael Ramirez; Lacerda, Luiz Gustavo; Carvalho Filho, Marco Aurélio da Silva; Bannach, Gilbert [UNESP]; Schnitzler, Egon (My University, 2011)
Starch is one of the most important sources of reserve of carbohydrate in plants and the main source in the human diet due to its abundance in the nature. There no other food ingredient that can be compared with starch in terms of sheer versatility of application in the food industry. Unprocessed native starches are structurally too weak and functionally too restricted for application in today’s advanced food and industrial technologies. The main objective of this study was to compare the thermal behavior of native cassava starch and those treated with hydrogen peroxide, as well as those treated with hydrogen peroxide and ferrous sulfate. The cassava starch was extracted from cassava roots (Manihot esculenta, Crantz) and treated by standardized hydrogen peroxide (H2 O2 ) solutions at 1, 2 and 3% (with or without FeSO4 ). Investigated by using they are thermoanalytical techniques: thermogravimetry - TG, differential thermal analysis – DTA and differential scanning calorimetry - DSC, as well as optical microscopy and X-ray powder diffractometry. The results showed the steps of thermal decomposition, changes in temperatures and in gelatinization enthalpy and small changes in crystallinity of the granules.
Keywords: Starch; Cassava; Hydrogen peroxide thermal analysis